Crown root ratio and angulation of various permanent teeth in patients with and without cleft lip/palate - Dolly Patel; Surina Sinha; Prerna Rupareliya; Diptesh Guha (Wolters Kluwer Medknow Publications, 2023)
Aims and Objectives: The purpose of this study was to analyze parameters of tooth in subjects with nonsyndromic cleft lip and palate (CLCP) and to compare the findings with the control groups. Teeth in the cleft-affected and nonaffected side in the same unilateral cleft lip and palate (ULCP) patient were also compared. Materials and Methods: The study included 200 subjects in the age group of 12-37 years who were divided into two groups: nonsyndromic CLCP and control group. The control group was further subdivided into skeletal Class I, II, and III subgroups based on ANB, AO-BO, and overjet, respectively. Crown height, root length, total tooth length, crown root ratio (C/R ratio), and tooth angulations of maxillary permanent central incisors, canines, 1st premolars, and 1st molar were measured on orthopantomograms using both ITK SNAP software and manual tracing. Results: Crown heights significantly increased while root lengths significantly decreased in the CLCP patients when compared to control groups. Total tooth lengths of central incisor, canine, and 1st premolar in CLCP patients were found to be decreased significantly. C/R ratios of all the teeth of nonsyndromic CLCP group irrespective of the cleft affected or nonaffected side was found to be increased as compared to the control groups. There was a significant difference seen in crown height, root length and mesiodistal tooth angulations in the cleft affected side when compared to the non affected side in a UCLCP patient's dentition. However the total tooth length and the C/R ratio were not affected. Conclusion: Common findings of CLCP are aberrant teeth development, altered tooth morphology, and malformed teeth. The severity of cleft has an impact on the tooth development and morphology as it was observed that delayed root development and short roots, decreased total tooth length, increased C/R ratio and variations in teeth angulations in CLCP patients were affected by the presence and severity of cleft.